(untitled) (Journal of Political Science, 2021)
This paper is a review based synthesis on the conceptual and theoretical debates on social movements (SMs). It aims to analyse the debate from different theoretical lens which are popularly used in the studies of SMs. The paper then explores prominent research issues that could be grounded at the local contexts of the movements. The main argument of the paper is that the discourse of SM is not linear and monolithic. Rather, it is a poly centric notion and thus essentially contested in terms of theorization and research.